Designing musical soundtracks for Brain Controlled Interface (BCI) systems - Ramchum, Richard; Chamberlain, Alan; Benford, Steve (2018)
This paper presents research based on the creation and development of two Brain Controlled Interface (BCI) based film experiences. The focus of this research is primarily on the audio in the films; the way that the overall experiences were designed, the ways in which the soundtracks were specifically developed for the experiences and the ways in which the audience perceived the use of the soundtrack in the film. Unlike traditional soundtracks the adaptive nature of the audio means that there are multiple parts that can be interacted with and combined at specific moments. The design of such adaptive audio systems is something that is yet to be fully understood and this paper goes someway to presenting our initial findings. We think that this research will be of interest and excite the Audio-HCI community.